Atmospheric composition in the Eastern Mediterranean: Influence of biomass burning during summertime using the WRF-Chem model. (May 2016) - Bossioli, E.; Tombrou, M.; Kalogiros, J.; Allan, J.; Bacak, A.; Bezantakos, S.; Biskos, G.; Coe, H.; Jones, B.T.; Kouvarakis, G.; Mihalopoulos, N.; Percival, C.J.
Abstract: The composition of the atmosphere over the Aegean Sea (AS) during an 'Etesian' outbreak under the influence of biomass burning (BB) activity is investigated. Simulations with the fully coupled WRF-Chem model during the Aegean-GAME campaign (29/8-9/9/2011) are used to examine the BB effect over the region. Two distinct Etesian flow patterns characterized by different transport conditions are analysed. The influence of the off-line calculated BB emissions on the atmospheric chemical composition over the AS under these conditions is estimated. In addition, sensitivity runs are used to examine the influence of the biogenic emissions calculated on-line and the realistic representation of the stratosphere-troposphere exchange processes are investigated through the time-varying chemical boundary conditions from the MOZART global chemical transport model. The horizontal and vertical distributions of gaseous and aerosol species are simulated under long-range transport conditions and interpreted in relation to the evolution of the Planetary Boundary Layer (PBL). In the case of a weaker synoptic system (medium-range transport conditions), even a small variability of meteorological parameters in limited areas become critical for the spatial distribution of gases and aerosols. The BB activity increases O3, PM2.5 and organic matter concentrations up to 5.5 ppb, 5.8 μg m −3 and 3.3 μg m −3, respectively. The spatial extent of the simulated BB plumes is further examined by comparison with airborne measurements of hydrogen cyanide (HCN). The estimated effect of biogenic emissions on O3 and PM2.5 concentrations is either positive or negative (±6 ppb for O3 and up to ± 1 μg m −3 for PM2.5 ) depending on the emission algorithm employed. The realistic representation of the chemical boundary conditions reproduces an observed layer rich in O3 above 4 km, but also increases O3 concentrations inside the PBL by up to 40%. Highlights: The Etesian flow pattern determines the distribution of aerosols over the AS. The Etesian flow pattern determines the paths of biomass burning (BB) emissions. The BB activity increases PM2.5 concentrations up to 5.8 μg m −3 . The effect of the biogenic emissions is evident inside/above the PBL. Simulations with MOZART boundaries increase O3 by 50%.